Pengaruh Perbedaan Varietas Rumput Laut (Kappaphycus sp) dan Variasi Kedalaman Terhadap Pertumbuhan dan Produksi Rumput Laut Menggunakan Metode Budidaya “Top Down” - A.R.Tassakka, Asmi Citra Malina; Latama, Gunarto; Rustam, Rustam (Torani Journal of Fisheries and Marine Science, 2014)
The objective of this study was to investigate the effect of different types of Seaweed (Kappaphycus sp) and depth variation on the growth, production and carrageenan content of Seaweed using a top down cultivation method. Top down method combined the two methods of cultivation, the method of surface and off-bottom method. The types of Seaweed used were Kappaphycus alvarezii (Brown Maumere and Local Maumere) and Bali Seaweed (Kappaphycus striatum). This study was designed using a factorial experimental design, where is comprised of two factors: the types and water depth.  Parameters measured were daily growth rate, production and carrageenan content of Seaweeds.  The results showed that different types of Seaweed gave a significant effect (P<0.05) on daily growth rate and production of Seaweeds, however depth variation did not give a significant effect on daily growth rate and production of Seaweeds (P>0.05).  A combination of Seaweed types and depth variation did not give a significant effect on daily growth rate and production of Seaweeds (P>0.05). The highest carrageenan content was found in Local Seaweed (42.15%).  Brown Seaweed produced 40.59% of carrageenan content while Bali Seaweed produced 35.80%.